2019
DOI: 10.1158/1078-0432.ccr-18-3659
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals Prognostic Molecular Signatures of Stage I Melanoma

Abstract: Purpose: Previously identified transcriptomic signatures have been based on primary and metastatic melanomas with relatively few American Joint Committee on Cancer (AJCC) stage I tumors, given difficulties in sampling small tumors. The advent of adjuvant therapies has highlighted the need for better prognostic and predictive biomarkers, especially for AJCC stage I and stage II disease.Experimental Design: A total of 687 primary melanoma transcriptomes were generated from the Leeds Melanoma Cohort (LMC). The pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 37 publications
7
39
1
Order By: Relevance
“…The published signatures from Thakur et al (16) (LMC_150; n=150 genes) as well as those from Gerami et al (12) (Decision-Dx Melanoma™; n=27 genes) were not found to be significantly associated with survival in multivariate models in our dataset, which may in part be reflective a higher proportion of stage III patients in these data than in these earlier studies (Supplementary figure S7).…”
Section: Resultscontrasting
confidence: 64%
See 4 more Smart Citations
“…The published signatures from Thakur et al (16) (LMC_150; n=150 genes) as well as those from Gerami et al (12) (Decision-Dx Melanoma™; n=27 genes) were not found to be significantly associated with survival in multivariate models in our dataset, which may in part be reflective a higher proportion of stage III patients in these data than in these earlier studies (Supplementary figure S7).…”
Section: Resultscontrasting
confidence: 64%
“…In particular, we found that adding the signature to the clinical covariates correctly predicted an additional 42 cases (Figure 1E). We then tested the performance of published prognostic signatures from Gerami et al (12) (Decision-Dx Melanoma™; n=27 genes) and Thakur et al (16) (LMC_150; n=150 genes) using the same machine learning models in our dataset and were not able to deduce that these signatures perform better than the baseline clinical covariates at the 5% significance level (Supplementary figure S4 & Supplementary table S3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations